Changes in Energy Metabolism Trigger Pupal Diapause Transition of Bactrocera minax After 20-Hydroxyecdysone Application - Dong, Yong-Cheng; Chen, Zhen-Zhong; Clarke, Anthony R.; Niu, Chang-Ying (Frontiers in Physiology, 2019)
Correct timing of diapause entry and exit is critical for a species’ survival. While many aspects of insect diapause are well studied, the mechanisms underlying diapause termination remain largely unknown. Chinese citrus fly, Bactrocera minax, is a univoltine insect with an obligatory pupal diapause. The application of 20-hydroxyecdysone (20E) is known to terminate diapause in B. minax and we used this approach, along with isobaric tag for relative and absolute quantitation technology, to determine the proteins associated with diapause termination in this fly. Among 2258 identified proteins, 1169 proteins significantly differed at 1-, 2-, and 5-days post injection of 20E, compared with the solvent-injected control group. Functional annotation revealed that the majority of differentially-expressed proteins were enriched in core energy metabolism of amino acids, proteins, lipids and carbohydrates, and signal transduction pathways including PPAR signalling, Calcium signalling, Glucagon signalling, VEGF signalling, Ras signalling, cGMP-PKG signalling and cAMP signalling. A combined transcriptomic and proteomic analyses suggested the involvement of energy metabolism in the response of diapause transition. RNA interference experiments disclosed that 20E injection triggers diapause termination probably through non-genomic actions, rather than nuclear receptor mediated genomic actions. Our results provide extensive proteomic resources for insect diapause transition and offer potential for pest control by incapacitate the regulation of diapause termination either breaking diapause prematurely or delaying diapause termination to render diapausing individuals high risk of mortality.